The application of Global Trigger Tool in monitoring antineoplastic adverse drug events: a retrospective study - Liu, Yang; Liu, Xianjun; Xia, Binbin; Chen, Jing; Sun, Wenfang; Liu, Fang; Cheng, Hua (Frontiers in Oncology, 2024)
Objective This study aimed to establish an antineoplastic drugs trigger tool based on Global Trigger Tool (GTT), to examine the performance by detecting cancer patients adverse drug events (ADEs) in a Chinese hospital (a retrospective review), and to investigate the factors associating with the occurrence of antineoplastic ADEs. Methods Based on the triggers recommended by the Global Trigger Tool and those used in domestic and foreign studies, and taking into account the scope of biochemical indexes in our hospital, some of them were adjusted. A total of 37 triggers were finally developed. 500 medical records of oncology patients discharged in our hospital from June 1, 2020 to May 31, 2021 were randomly selected according to the inclusion and exclusion criteria. These records were reviewed retrospectively by antineoplastic drugs trigger tool. The sensitivity and specificity of the triggers were analyzed, as well as the characteristics and risk factors for the occurrence of ADEs. Results 33 of the 37 triggers had positive trigger, and the sensitivity was 91.8% (459/500). The specificity : the positive predictive value (PPV) of overall ADEs was 46.0% (715/1556), the detection rate of ADEs was 63.0% (315/500), and the ADEs/100 admissions was 136.0(95%CI:124.1-147.9), the ADEs/1000 patient days was 208.33(95%CI:201.2-215.5). The top three antineoplastic drugs related to ADEs were antimetabolic drugs (29.1%), plant sources and derivatives (27.1%), and metal platinum drugs (26.3%). The hematologic system was most frequently involved (507 cases, 74.6%), followed by gastrointestinal system (89 cases, 13.1%). Multivariate logistic regression analysis showed that the number of combined drugs (OR=1.14, 95%CI: 1.07-1.22, P < 0.001) and previous history of adverse drug reaction (ADR)(OR=0.38, 95%CI: 0.23-0.60, P < 0.001) were risk factors for ADEs. Length of hospital stay (OR=0.40, 95%CI: 0.14-1.12, P < 0.05) and previous history of ADR (OR=2.18, 95%CI: 1.07-4.45, P < 0.05) were risk factors for serious adverse drug events (SAE). Conclusion The established trigger tool could be used to monitor antineoplastic drugs adverse events in tumor patients effectively, but still need to be optimized. This study may provide some references for further research in order to improve the rationality and safety of antineoplastic medications.